Analysis of Textual Realization in Genre Description and Explanation by Students of Samudra University - Husni Az-Zhahir; T. Silvana Sinar; T. Thyrhaya Zein (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This article discusses the Linguistic features found in the text description and explanation of the events or cultural activities of Aceh in the city of Langsa. The purpose of this research is to examine the realization of textual features in the text description and explanation. The method used in this research is descriptive-qualitative, qualitative research is a research procedure that produces descriptive data in the form of words written or spoken from people or behaviors that can be observed '. The data of this study are linguistic units in the form of clauses derived from 10 written texts of genre description and explanation by fifth semester students, English Education Study Program at the Faculty of Teacher Training at Samudra Langsa University. The analysis is carried out based on the functional systemic linguistic theory (LSF) framework, with the analytical construct formulated. The findings of this study are complex theme types, including markers such as: and, and then, when, becouse, cause, after that, before that, if, so, while, that and next. These markers function as conjunctions, connectors and successors. Of all these markers, contained in the text, only the "and then" markers are the most dominant markers.